2009
DOI: 10.1002/art.24999
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of Cyr61 in interleukin‐17–dependent proliferation of fibroblast‐like synoviocytes in rheumatoid arthritis

Abstract: Objective. Fibroblast-like synoviocytes (FLS) are a major component of the hyperplastic synovial pannus that aggressively invades cartilage and bone during the course of rheumatoid arthritis (RA). Cyr61 (CCN1) is a product of a growth factor-inducible immediate early gene and is involved in cell adhesion, proliferation, and differentiation. However, the role that Cyr61 plays in FLS proliferation has remained undetermined. The aim of this study was to identify the role of Cyr61 in regulating the proliferation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
139
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 39 publications
8
139
0
1
Order By: Relevance
“…Previous studies have implicated CYR61 in the pathogenesis of inflammatory diseases, including rheumatoid arthritis (RA), and a microarray analysis of B cells from monozygotic twins revealed a significantly higher expression of CYR61 in the twin with RA compared to the healthy twin (29). CYR61 is also overexpressed in RA synovial tissue and plays a critical role in the proliferation of rheumatoid arthritis synovial fibroblasts (30). CYR61 expression is induced in human skin dermal fibroblasts after exposure to cigarette smoke (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated CYR61 in the pathogenesis of inflammatory diseases, including rheumatoid arthritis (RA), and a microarray analysis of B cells from monozygotic twins revealed a significantly higher expression of CYR61 in the twin with RA compared to the healthy twin (29). CYR61 is also overexpressed in RA synovial tissue and plays a critical role in the proliferation of rheumatoid arthritis synovial fibroblasts (30). CYR61 expression is induced in human skin dermal fibroblasts after exposure to cigarette smoke (31).…”
Section: Discussionmentioning
confidence: 99%
“…A complementary DNA microarray analysis of B cells from monozygotic twins revealed significantly higher expression of Cyr61 in twins with RA compared with their healthy cotwins, and that study also showed increased immunoreactivity of Cyr61 in synovial tissue of RA patients (13). Recently, Zhang et al (14) found that Cyr61 plays a critical role in IL-17-mediated proliferation of fibroblast-like synoviocytes in RA. Nevertheless, whether Cyr61 is involved in inflammatory signaling of osteoblasts in RA remains to be elucidated.…”
mentioning
confidence: 88%
“…In a recent report, Zhang and colleagues made a critical observation that IL-17 induces the proliferation of fibroblast-like synoviocytes (FLS) derived from patients with rheumatoid arthritis (RA), by up-regulating Cyr61 expression (2). They have also analyzed the signaling mechanism for this pathway and have observed that IL-17 induces Cyr61 through the p38 MAPK and NF-B pathways.…”
Section: Interleukin-17-induced Proliferation Of Fibroblast-like Synomentioning
confidence: 99%